Model Problem Based Learning Mempengaruhi Kemampuan Menyelesaikan Soal Cerita Matematika Siswa Kelas IV Sekolah Dasar - Ayu Fitri; Siti Fatimah (Jurnal Sekolah Dasar, 2019)
This study aims to determine the difference between the influence of the problem based learning model and those who do not use the problem based learning model on the ability to solve mathematical story problems for fourth grade students of Adiarsa Barat II Elementary School in 2018/2019. This research is a quantitative research with quasi experimental research type. With the sample used in this study amounted to 30 students with a population of 60 students. Data collection techniques using the ability to solve math problems in the form of essay questions. In testing the validity of the test the ability to solve mathematical story questions from 10 items all declared valid. The reliability test results obtained r11 finished 0.843. Hypothesis testing results, with the t-sig test (2 tailed) obtained 0.037 <0.05 with a tcount of 2.140> t table 1.699 then Ho is rejected, then it means there is a difference in the final value of the ability to solve mathematical story problems between students using the Problem Based Learning model with who do not use the Problem Based Learning model. The results of this study concluded that there was a difference in the influence of the Problem Based Learning model on the ability to solve math problems in grade IV SD Negeri Adiarsa Barat II in the 2018/2019